GEREJA UNIVERSAL DALAM ALKITAB: Universal Church in The Bible - Kasakeyan, Raimond Heintje (STT INDONESIA MANADO, 2021)
Understanding the concept of the church is essential in the history of Christianity. There are too many confusing teachings, thus clouding the view of Christians. The best approach to